Shift in serotype distribution of Shigella species in China, 2003–2013. (March 2015) - Qiu, S.; Xu, X.; Yang, C.; Wang, J.; Liang, B.; Li, P.; Li, H.; Yi, S.; Liu, H.; Cui, X.; Wu, Z.; Xie, J.; et al.
Abstract: We identified 2912 Shigella isolates from diarrhoeal patients in China during 2003–2013. The most common species was Shigella flexneri (55.3%), followed by Shigella sonnei (44.1%); however, S. sonnei is becoming increasingly prevalent. Among the S. flexneri isolates, serotypes 2a and X variant (-:7, 8, E1037) were the two most prevalent serotypes, and serologically atypical isolates were also commonly identified. Overall, S. sonnei, S. flexneri 2a and S. flexneri X variant (-:7, 8, E1037) accounted for 76.1% of all Shigella isolates, and their prevalence increased from 54.0% during 2003–2004 to 84.1% during 2011–2013. A change was observed in the serotype distribution of Shigella in China during this period, and we propose an ideal strategy to inform the development of a broadly effective Shigella vaccine candidate.